2005
DOI: 10.1111/j.1365-2656.2005.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the assumptions of the ideal despotic distribution with an unpredictable food supply: experiments in juvenile salmon

Abstract: Summary1. Models linking the behaviours of individual animals, their positions within socially complex groups and spatio-temporal variation in resource distribution offer a promising base for predicting population responses to changing environments. The ideal free and despotic distributions and their derivatives are particularly influential in this regard. 2. Due to the difficulties of conducting work in the wild, for some groups of animals such models are often based on observations of animals in small-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 52 publications
4
35
1
Order By: Relevance
“…This 302 distribution pattern resembled an Ideal Despotic Distribution (IDD), first described in birds, where 303 movement between patches was controlled by intraspecific competition (Fretwell, 1972). The IDD has 304 previously been described in laboratory situations in Salmonids, where dominant individuals excluded other 305 individuals from a favourable patch (Hakoyama and Iguchi, 2001;Maclean et al, 2005). In our study, 306 although behavioural quantifications of the individuals in the "dominant" tank were not carried out, 307 observation of the fish confirmed that they displayed agonistic behaviours towards other individuals in the 308 tank and fish attempting to enter the tank.…”
Section: Discussion 299mentioning
confidence: 47%
“…This 302 distribution pattern resembled an Ideal Despotic Distribution (IDD), first described in birds, where 303 movement between patches was controlled by intraspecific competition (Fretwell, 1972). The IDD has 304 previously been described in laboratory situations in Salmonids, where dominant individuals excluded other 305 individuals from a favourable patch (Hakoyama and Iguchi, 2001;Maclean et al, 2005). In our study, 306 although behavioural quantifications of the individuals in the "dominant" tank were not carried out, 307 observation of the fish confirmed that they displayed agonistic behaviours towards other individuals in the 308 tank and fish attempting to enter the tank.…”
Section: Discussion 299mentioning
confidence: 47%
“…Armstrong et al (1999) suggested that dominant parr settle in restricted territories, which they defend from intruders whereas subdominant parr adjust their positions and movements accordingly. However, a recent experimental study suggested that parr can also be dominant and move frequently between feeding locations; but parr tend to leave rich patches less frequently than they leave poor patches (Maclean et al 2005). In the present study, social relations of parr could not be analyzed but it may be hypothesized that parr could have held to different social status.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the variability observed in habitat use among individuals with respect to turbulence may be due to other habitat variables, which may override habitat selection based on turbulence (Heggenes 2002). Alternatively, there may be a strong preference for specific turbulence characteristics, but an individual may be forced by competition to use alternative habitat characterized by flow conditions other than those preferred (McLaughlin and Grant 1994;MacLean et al 2005;Kemp et al 2006). Whereas Atlantic salmon parr seem to react and respond to turbulence on a smaller microhabitat scale, the application of dynamic hydraulic variables on reach scale seem to not provide a useful tool for fisheries and habitat managers.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of time used for feeding decreases with the mean and SD of velocity (Enders et al 2005). However, on a local scale, parr may demonstrate only minor adjustments to habitat conditions as individual variation in habitat use HABITAT CHOICE BY ATLANTIC SALMON PARR is primarily affected by dominance status (MacLean et al 2005;Kemp et al 2006).…”
Section: Discussionmentioning
confidence: 99%